Efektivitas Pelaksanaan Program Prioritas Aladin Dalam Peningkatan Kesejahteraan Masyarakat Desa Sitiaji Bojonegoro - Achmad Dani Afifuddin Zuhri; Ertien Rining Nawangsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the effectiveness of the ALADIN Priority Program (roof, floor, and wall repairs) in improving the welfare of the community in Sitiaji Village, Sukosewu District, Bojonegoro Regency. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, with effectiveness indicators referring to Subagyo's theory, namely targeting accuracy, program socialization, achievement of program objectives, and program monitoring. The results show that the ALADIN program has been implemented effectively. Targeting accuracy was achieved well because the beneficiaries truly come from communities in need. Socialization went quite well, although there were still some obstacles in the reach of information. The program's objectives were achieved by improving the quality of houses, that have an impact on increasing the comfort and dignity of residents' lives. Program monitoring is also carried out systematically and periodically by the village government together with the technical team. Thus, the implementation of the ALADIN program is considered capable of making a real contribution to improving the welfare of the Sitiaji Village community.